Tom's Struggle For Love In 500 Days Of Summer: An Humanistic Psychological Perspective - Diyanti, Salistia Rohma; Nugroho, Abdillah (UNIVERSITAS PAKUAN, 2024)
This research uses Abraham Maslow's (1954) humanistic theory to examine Tom's struggle for love in the movie